2022
DOI: 10.3390/insects13070617
|View full text |Cite
|
Sign up to set email alerts
|

The Bugs in the Bags: The Risk Associated with the Introduction of Small Quantities of Fruit and Plants by Airline Passengers

Abstract: Among European countries, Italy is the most exposed to the risk of biological invasions, principally for its numerous entry points (ports and airports) and for climatic conditions favorable for the acclimatization of several invasive species. Here it was assessed that the greatest threats to our agro-ecosystems come mainly from the passenger baggage in which a variety of fruits and vegetables are carried. From 2016 to 2021, large quantities of plant products were found in the luggage of passengers travelling f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
16
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(16 citation statements)
references
References 65 publications
0
16
0
Order By: Relevance
“…On air transport, Pace et al (2022) reported the risks of introducing pests via air are not yet well studied, and their frequency may be underestimated. The data collected at three Border Control Points (BCPs) in Italy (Campania region) suggested that travellers are often unaware of the risks connected with the imports of plants, fruits, and vegetables.…”
Section: Levels Of Awarenessmentioning
confidence: 99%
See 2 more Smart Citations
“…On air transport, Pace et al (2022) reported the risks of introducing pests via air are not yet well studied, and their frequency may be underestimated. The data collected at three Border Control Points (BCPs) in Italy (Campania region) suggested that travellers are often unaware of the risks connected with the imports of plants, fruits, and vegetables.…”
Section: Levels Of Awarenessmentioning
confidence: 99%
“…Less frequent sources of information included biosecurity communications through social media (2% of tourists) and airport signage (2%). Pace et al, (2022), suggested that infographics or factsheets could be helpful to inform passengers about the risks of plant health transport, making them responsible for the transport of plants. Additionally, the authors suggested that the advertising campaign the European and Mediterranean Plant Protection Organisation (EPPO) was running at the time to raise public awareness and to stimulate responsible behaviour, should be updated each year with new potential plant and fruit health threats.…”
Section: Preferred Sources Of Informationmentioning
confidence: 99%
See 1 more Smart Citation
“…In a study focusing on invasive species intercepted at three Border Control Points (BCPs; two ports and one airport) in Italy (Campania region) from 2016 to 2021, Pace et al (2022) found that during this period "large quantities of plant products were found in the luggage of passengers travelling from outside the EU and seized at the BCPs". Results suggested very high risk for possible introduction of threatening pests through luggage from air passengers, and the authors noted that there is lack of sufficient data on the risk and that its frequency is underestimated.…”
Section: The Curious Travellermentioning
confidence: 99%
“…Invasive insects and pathogens represent an increasing threat to agriculture and forestry worldwide 1 , 2 . Despite the implemented preventative measures, the transport of goods (stored products, living plants and fruits), and people facilitate the introduction of invasive species in new areas 3 , 4 . And climate change promotes modification in the distribution range of pests and can cause the weakening of host plants and a higher level of damage by pests 5 , 6 .…”
Section: Introductionmentioning
confidence: 99%